2013
DOI: 10.1111/bph.12366
|View full text |Cite
|
Sign up to set email alerts
|

HDAC inhibitors restore C‐fibre sensitivity in experimental neuropathic pain model

Abstract: BACKGROUND AND PURPOSEHypoesthesia is a clinical feature of neuropathic pain. The feature is partly explained by the evidence of epigenetic repression of Nav1.8 sodium channel in the dorsal root ganglion (DRG). EXPERIMENTAL APPROACHWe investigated the possibility of trichostatin A (TSA), valproic acid (VPA) and suberoylanilide hydroxamic acid (SAHA) to reverse the unique C-fibre sensitivity observed following partial ligation of sciatic nerve in mice. KEY RESULTSNerve injury-induced down-regulation of DRG Nav1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 39 publications
(57 reference statements)
1
53
0
1
Order By: Relevance
“…There are overlapping indications among the best ones for different druggable protein classes suggesting the systems level interplay for these diseases. To verify our predictions of particular druggable classes being involved in the pathways for pathogenesis or treatment of selected indications with high CANDO accuracies, we collected independent evidence from existing literature [28, 52-94], which is summarized in (Supplementary Table S1 ). As an example, the indication congenital limb deformities has high CANDO accuracy with the kinases and ligases protein sets (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There are overlapping indications among the best ones for different druggable protein classes suggesting the systems level interplay for these diseases. To verify our predictions of particular druggable classes being involved in the pathways for pathogenesis or treatment of selected indications with high CANDO accuracies, we collected independent evidence from existing literature [28, 52-94], which is summarized in (Supplementary Table S1 ). As an example, the indication congenital limb deformities has high CANDO accuracy with the kinases and ligases protein sets (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in the PSL model, SAHA (5 mg/kg, i.p., once daily from day 3 to day 9 after nerve injury) restored C-fiber sensitivity at day 1 of SAHA treatment (day 3 of injury) until day 9 of injury. Moreover, SAHA reversed injury-induced repression of Na v 1.8, TRPA1 and TRPM8 expression, but not that of CGRP (Matsushita et al, 2013).…”
Section: Hydroxamatesmentioning
confidence: 85%
“…For example, decreased expression of -opioid receptors (MORs) and Na v 1.8 sodium channels in the DRG is thought to be an underlying cause of neuropathic pain symptoms (Uchida et al, 2010). It has also been reported that reductions in MOR and Na v 1.8 activity are related to enhanced H4 acetylation at the neuron-restrictive silencer factor (NRSF) promoter region, reduction of H3 and H4 acetylation at the MORneuron-restrictive silencer element (NRSE) and at Na v 1.8-NRSE-2, and enhanced H3 acetylation at Na v 1.8-NRSE-1 (Matsushita et al, 2013). Further evidence suggests that histone acetylation in the promoter of the brain derived neurotropic factor (BDNF) gene was significantly enhanced in the DRG and spinal cord in pain models of partial sciatic nerve ligation (PSL) and CCI, as well as during chronic morphine treatment.…”
Section: Dynamic Changes Of Hdac Expression and Histone Acetylation Lmentioning
confidence: 98%
See 1 more Smart Citation
“…All of these changes were found positively correlated to the changes in hypersensitivity of C-fibers, instead of Aβ- and Aδ-fibers. Recently they found that downregulated Nav1.8 mRNA in the injured DRGs was reversed by intraplantar injection of HDACi, VPA or TSA, following one pre-surgery dose and daily dose after surgery for 3 days [164]. This finding suggests that class I and IIa HDAC are involved.…”
Section: Introductionmentioning
confidence: 99%